Effectiveness of Oxalis corniculata L. Ethanol Extract against Mono-Species of Biofilm Staphylococcus aureus - Hasyrul Hamzah; Khalish Arsy Al Khairy Siregar; Ari Nurwijayanto; Retno Wahyuningrum; Seftika Sari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Inappropriate administration of antibiotics can cause resistance to bacteria. Staphylococcus aureus is one of the strong biofilm-forming bacteria that cause antibiotic resistance. Calincing (Oxalis corniculata L.) leaves have excellent antibacterial activity, but their antibiofilm activity against S. aureus has not been reported until now. Currently, the discovery of new antibiofilm against S. aureus biofilms is significant to prevent the impact of infections caused by biofilms. This study was intended to determine the effectiveness of the ethanol extract of O. corniculata leaves in inhibiting and eradicating S. aureus biofilm formation. Planktonic testing, inhibition, and biofilm eradication activity were carried out using the microtiter broth method. Antibiofilm activity of O. corniculata leaves against S. aureus biofilm was analyzed by calculating the minimum concentration of biofilm inhibitor (MBIC50) and minimum biofilm eradication concentration (MBEC50). Data were analyzed using the Statistical Package for the Social Sciences (SPSS) with a 95% confidence level. Oxalis corniculata leaves showed inhibitory activity on the formation of the tested S. aureus biofilm. The ethanol extract of 1% O. corniculata leaves gave 76.23±0.01% antibacterial activity of S. aureus and 71.32±0.01% of mid-phase antibiofilm activity, and 69.33±0.01% maturation phase. The results also prove that the ethanolic extract of O. corniculata leaves can eradicate S. aureus biofilm formation. Therefore, the ethanol extract of O. corniculata leaves can be developed as a new antibiofilm against S. aureus.